Clients as “Partial” Employees of Service Organizations: Role Development in Client Participation - Mills, Peter K.; Morris, James H. (Academy of Management Review, 1986)
Clients of service organizations have important roles to perform in creating services. Yet, comparatively little attention has been directed at the participation of clients in complex and demanding client performance domains. In this paper, clients are viewed as “partial” employees and (1) a model of client involvement stages is proposed, (2) role definition and control for clients in complex service creation are discussed, and (3) attention to issues that emerge from this discussion is encouraged.